2021
DOI: 10.1002/lol2.10206
|View full text |Cite
|
Sign up to set email alerts
|

Flow intermittence alters carbon processing in rivers through chemical diversification of leaf litter

Abstract: The dry phase of intermittent rivers promotes the accumulation of leaf litter on various terrestrial and aquatic habitats. This environmental heterogeneity causes a chemical diversification of leaf litter by a range of physical and biological degradation processes acting across the various habitats. After flow resumption, the chemically diversified leaves are mixed and subject to continued decomposition downstream. We hypothesized that the chemical diversification of leaf litter during the dry phase would affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
(79 reference statements)
0
15
0
Order By: Relevance
“…Although the negative effects of flow intermittence on decomposition can be linked to changes in leaf resource nutritional quality (del Campo et al 2021a), most field studies attribute these negative effects to losses of primary consumers such as shredders (Datry et al 2011, Schlief and Mutz 2011, Abril et al 2015, Northington and Webster 2017. We found that increasing flow intermittence had a seasonal positive effect on instream resource quality and quantity, but the negative effects on invertebrate richness and shredder abundances drove the associated decreases in decomposition.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Although the negative effects of flow intermittence on decomposition can be linked to changes in leaf resource nutritional quality (del Campo et al 2021a), most field studies attribute these negative effects to losses of primary consumers such as shredders (Datry et al 2011, Schlief and Mutz 2011, Abril et al 2015, Northington and Webster 2017. We found that increasing flow intermittence had a seasonal positive effect on instream resource quality and quantity, but the negative effects on invertebrate richness and shredder abundances drove the associated decreases in decomposition.…”
Section: Discussionmentioning
confidence: 61%
“…dictated by the unidirectional flow of water), downstream ecosystem functions may thus depend on the disturbance regime inand connectivity to -upstream habitats. An intermediate amount of upstream intermittence could therefore promote downstream decomposition rates by providing 1) pulses of high quality leaf resources and 2) influx of diverse species best adapted to resource use, from a variety of upstream habitats, following rewetting events (Northington and Webster 2017, del Campo et al 2021a, Catalàn et al 2022.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increases in C emissions from rivers, streams, and lakes are modest when dried areas are included in their global CO 2 emission estimates (Table 4), but represent a source of high variability in seasonal emissions (Liu et al, 2022). Furthermore, dried areas accumulate terrestrial leaf litter that, upon rewetting, can be rapidly mobilized and decomposed, contributing a CO 2 pulse equal to up to 10% from all permanent rivers and streams (Datry et al, 2018;del Campo et al, 2021). These changes in the spatial coverage and duration of dried areas, especially for highly variable small streams and ponds, (Evans et al, 2012).…”
Section: Precipitationmentioning
confidence: 99%